Penerapan Metode Shared Reading Untuk Meningkatkan Minat Baca - Siti Dini Fakhriya (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This article is a literature review to find out the concept of shared reading and its application in order to increase reading interest. Indonesian people's reading interest is relatively low, in order to improve literacy culture can be started by forming reading habits in children. Shared reading is a reading strategy that involves collaborative activities using books to read together. To be able to maximize the use of the shared reading method, several forms of implementation can be carried out such as the use of media and technology, making dictionaries, availability of reading materials and class setting. Shared reading can give children a pleasant experience in reading, introduce them to books, the meaning of reading and form their own reading habits.